The process of pollen transformation into bee bread: changes in bioactivity, bioaccessibility, and microbial dynamics - Degirmenci, Atiye; Yildiz, Oktay; Boyraci, Gulsum Merve; Er Kemal, Mehtap; Simsek, Omer (ROYAL SOC CHEMISTRY, 2024)
Bee pollen and bee bread go hand in hand with health-promoting functional food consumption. Although many studies report high bioactivities of those products, the biotransformation of pollen into bee bread has not been fully understood. Limited findings are available about polyphenol bioaccessibility and microbiological interactions during the fermentation process. This study evaluated the microbial flora, antioxidant properties, and polyphenol and soluble protein bioaccessibility of pollen and bee bread harvested from the same apiary over a certain timeline. Total phenolic content, antioxidant activity and soluble protein content were reported using an in vitro digestion model involving post-gastric, serum-available, and colon-available fractions. The results obtained with the in vitro digestion model refer to the effect of the harvesting period on greater bioaccessibility of polyphenols in bee bread than in pollen at the same apiary. Lactic acid bacteria and yeast found in the samples were mostly identified as Lactobacillus kunkeei, Leuconostoc pseudomesenteroides, and Candida magnoliae using matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). The discrimination between the pollen and bee bread samples collected in the same apiary and at different harvesting periods was also revealed by Principal Component Analysis (PCA). A harvesting time-based approach was applied to the biotransformation process of pollen and bee bread, and insights into microbial dynamics and bioaccessibility were revealed for the first time under the same beehive conditions. Bee pollen and bee bread go hand in hand with health-promoting functional food consumption.
Keywords: LACTIC-ACID BACTERIA; VITRO GASTROINTESTINAL DIGESTION; TOTAL ANTIOXIDANT ACTIVITY; MALDI-TOF MS; IDENTIFICATION; POLYPHENOLS; PROTEIN; FOOD; DIGESTIBILITY; LACTOBACILLUS; Biochemistry & Molecular Biology; Food Science & Technology